Islamic Education Insights: TGKH. Muhammad Zainuddin Abdul Madjid's Vision for the 21st Century - Tamim, Ahmad; Suhartini, Andewi (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
This study explores Maulana Syaikh Zainuddin's thoughts on Islamic education and its relevance in addressing the challenges of globalization in the 21st century. Using a qualitative approach, the research examines his perspective, which blends Islamic education values with general education as a unified whole. The findings highlight that Maulana Syaikh Zainuddin's concept of Islamic education provides an effective solution to equip the younger generation with self-protection against the impacts of globalization. He emphasized the importance of character building through a holistic approach, combining academic excellence with strong spirituality. His educational philosophy aims not only for worldly success but also for spiritual closeness to Allah SWT. This approach is crucial for fostering a generation that is resilient morally, intellectually, and spiritually in the face of globalization. The study contributes an applicable Islamic educational model that balances modernity with traditional Islamic values, fostering a globally competitive generation grounded in Islamic identity.